A highly concentrated electrolyte for high-efficiency potassium metal batteries - Xu, Wenxin; Wang, Huwei; Hu, Junyang; Zhang, Haodong; Zhang, Biao; Kang, Feiyu; Zhai, Dengyun (Chemical communications (Cambridge, England), 2021)
We report a highly concentrated electrolyte consisting of 4 M potassium bis(fluorosulfonyl)imide (KFSI) in diethylene glycol dimethyl ether (DEGDME). This new electrolyte enables stable cycling of K metal anodes with a high CE (over 98% over 400 cycles), and excellent capacity retention (99.7% after 500 cycles) of K||potassium Prussian blue (KPB) batteries. A highly concentrated electrolyte enables dendrite-free cycling of K metal anodes with a high CE (over 98% over 400 cycles).